Smokeless Tobacco Consumption and Oral Cancer: A Case-Control Study - Lucky, Jesmin Sultana; Islam, Md Ziaul (Journal of Preventive and Social Medicine, 2025)
Background: Smokeless tobacco consumption leads to oral cancer, which is a substantial source of morbidity and mortality in Bangladesh. This study was conducted to determine the association between smokeless tobacco consumption and the risk of oral cancer. Methods: It was a case-control study. Participants with oral cancer were considered cases, while those without oral cancer were regarded as controls. Data were collected through face-to-face interviews and reviews of the medical records through a pretested semi-structured questionnaire and checklist. Results: Tobacco consumption was significantly (p<0.05) higher among the cases (93.3%) than in the controls (30.7%). Oral cancer was found 31.6 times (OR=31.6, 95% CI 15.26- 65.64) more likely to develop among the cases than the controls. Smokeless tobacco was 18 times (OR = 18.00, 95% CI 7.18- 45.10) more likely to develop oral cancer than smoked tobacco. On the other hand, consumption of Sadapata and Gul were 15.4 times (OR=15.4, 95% CI 2.02-118.47) more likely to develop oral cancer than betel quid with Zarda consumption. Consumption of Betel Quid with Zarda more than 7 times per day was found 5.3 times (OR=5.3, 95% CI 0.52– 35.9) more likely to develop oral cancer among the cases than the controls. Conclusion: Smokeless tobacco consumption was significantly associated with the occurrence of oral cancer. The study recommends specific strategic actions to reduce tobacco consumption for the prevention of oral cancer. JOPSOM 2024; 43(1): 15-26